Preparation and application of hollow molecularly imprinted polymer

Hollow microporous network adsorption materials were synthesized by HF corrosion method, and hollow molecular imprinted polymers were obtained through surface molecular imprinting technology, which solved the problem of inaccessibility of pores within existing materials and achieved efficient adsorption and enrichment of food and environmental pollutants set.

CN119431797AActive Publication Date: 2025-02-14NANKAI UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310975091.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-04
Publication Date
2025-02-14
Estimated Expiration
2043-08-04

AI Technical Summary

Technical Problem

The internal pores of existing microporous organic network materials are difficult to get close and cannot play an effective role, resulting in limited application in food detection and contaminant adsorption.

Method used

Hollow microporous network adsorption materials were synthesized by HF corrosion method, and hollow molecular imprinted polymers were obtained through surface molecular imprinting technology to improve the porosity utilization and adsorption performance of the material.

Benefits of technology

The selective adsorption and efficient enrichment of food and environmental pollutants is achieved. The hollow structure of the material improves the density and adsorption efficiency of the imprinting site, and is suitable for the adsorption and enrichment of a variety of food pollutants.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119431797A_ABST
    Figure CN119431797A_ABST
Patent Text Reader

Abstract

The invention relates to preparation and application of a hollow molecularly imprinted polymer, a magnetic composite microporous network adsorption material with strong adsorbability and large specific surface area is firstly prepared, then a hollow microporous network adsorption material is synthesized through HF corrosion, and finally a hollow molecularly imprinted polymer adsorption material is obtained through surface molecular imprinting. The prepared hollow molecularly imprinted polymer can realize selective adsorption and efficient enrichment of food and environmental pollutants. Due to the advantages of larger specific surface area, stronger hydrophobicity and the like, the material has great potential as a harmful substance adsorption material. The stable application of the composite material in a complex food matrix is ensured, so that the selective enrichment and convenient management and control of target pollutants are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of material technology, and in particular relates to the preparation and application of a hollow molecular imprinted polymer. Background Art

[0002] Food safety is an important factor in protecting human health, and food testing technology is the technical support for protecting people's lives. Therefore, it is particularly important to quickly improve food testing technology, enhance food safety awareness, and strictly conduct food testing to create a healthy and safe food environment for the public.

[0003] Molecularly imprinted polymers (MIPs) are a type of selective functional polymer material. They use the target compound as a template molecule, simulate the molecular recognition between "antigen-antibody", and show selective recognition ability for the template molecule. In recent years, due to its advantages such as good affinity, high selectivity, strong anti-interference, and long service life, it has been widely used in the specific recognition of target molecules in food. Microporous organic network materials (MONs) are emerging microporous materials composed of aromatic alkynes and halides. The prepared MONs have a high pore strength, but it mainly comes from the surface pores of MONs, while most of the internal pores cannot function because they are difficult to access. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a preparation and application of a hollow molecular imprinted polymer.

[0005] The technical scheme adopted by the present invention is: a method for preparing a hollow molecular imprinted polymer, preparing a magnetic composite microporous network adsorption material, synthesizing a hollow microporous network adsorption material through HF corrosion, and then obtaining a hollow molecular imprinted polymer adsorption material through surface molecular imprinting.

[0006] Preferably, the specific steps include:

[0007] Step 1: Prepare magnetic composite microporous organic framework material by in-situ growth method;

[0008] Magnetic Fe 3 O 4 Preparation: FeCl 3 6H 2 O, anhydrous sodium acetate, ethylene glycol were mixed and subjected to hydrothermal reaction at 200℃, and the product was washed and dried to obtain magnetic Fe 3 O 4 ;

[0009] Magnetic Fe 3 O 4 @SiO 2 Preparation: Take 1.0g magnetic Fe 3 O4 , add 200mL HCl, ultrasonically treat, rinse the product, add 80mL ultrapure water, 320mL ethanol, 5mL ammonia water, ultrasonically treat; then add 1mL TEOS, stir mechanically, collect the product with a magnet, and obtain magnetic Fe 3 O 4 @SiO 2 ;

[0010] Magnetic Fe 3 O 4 @SiO 2 @UiO-66-NH 2 Preparation: Take 150 mg of magnetic Fe 3 O 4 @SiO 2 , add 300 mg zirconium (IV) chloride, 75 μL water, and 30 mL DMF, stir, add 2-aminoterephthalic acid, stir and dissolve; perform hydrothermal reaction at 120 °C, collect brown-black magnetic microspheres after the reaction is completed, rinse and dry to obtain magnetic Fe 3 O 4 @SiO 2 @UiO-66-NH 2 ;

[0011] Magnetic Fe 3 O 4 @SiO 2 @UiO-66-NH 2 @MON preparation: Take 200 mg Fe 3 O 4 @SiO 2 @UiO-66-NH 2 15 mL of toluene, 15 mL of triethylamine and a catalyst were added, and after complete dispersion, the mixture was mechanically stirred at 90 ° C for 0.5 h, 50 mg of tetrakis (4-ethynylphenyl) methane and 80 mg of 1,4-diiodobenzene were added, and the mixture was heated at 90 ° C for 6 h. After the reaction was completed, the product was collected with a magnet, washed and dried to obtain a magnetic composite microporous network adsorption material Fe 3 O 4 @SiO 2 @UiO-66-NH 2 @MON;

[0012] Step 2: Synthesize hollow microporous network adsorption material by HF corrosion; Take 100.0 mg Fe 3 O 4 @SiO 2 @UiO-66-NH 2 @MON, add 10 ml HF (5%) and react for 15 min, wash and dry to obtain the hollow structure microporous network adsorption material HMON;

[0013] Step 3: Obtain hollow molecular imprinting polymer adsorption material by surface molecular imprinting; add 1mmol DT to a mixture of 25mL acetonitrile and 5mL water and mix well, add functional monomer (APTES), crosslinker (TEOS) and ammonia water into the system at a ratio of 1:4:9; after mixing evenly, add 3mL HMON dispersed in acetonitrile; remove oxygen from the reaction system and stir at room temperature overnight, and the obtained precipitate is the hollow molecular imprinting polymer HMON@MIP.

[0014] Preferably, in step 1, magnetic Fe is prepared 3 O 4 @SiO 2 @UiO-66-NH 2 The catalyst used in @MON was 3.4 mg of bis(triphenylphosphine)palladium(II) dichloride and 1.0 mg of cuprous iodide.

[0015] Preferably, the drying temperature is 50-60°C.

[0016] Preferably, in step 3, the product obtained by stirring overnight is washed with methanol and water, and then eluted with a Soxhlet extraction apparatus, and the eluent consists of acetone and acetic acid (9:1, v / v).

[0017] The invention discloses a hollow molecular imprinted polymer prepared by a method for preparing the hollow molecular imprinted polymer.

[0018] Application of hollow molecularly imprinted polymers in the adsorption or detection of food or environmental pollutants.

[0019] Preferably, the obtained hollow molecularly imprinted polymer material is placed in a target solution to achieve adsorption or enrichment of pollutants.

[0020] Preferably, the adsorbed hollow molecularly imprinted polymer can be used again for adsorption or enrichment of pollutants after being eluted with an eluent.

[0021] The advantages and positive effects of the present invention are as follows: the hollow molecular imprinted polymer prepared by the method has uniform porosity, large specific surface area, stable chemical properties, and significant specific adsorption capacity for target pollutants; by providing the optimal reaction ratio and reaction conditions, the hollow structure of the material greatly increases the density of imprinted sites, thereby improving the adsorption efficiency, and the hollow molecular imprinted polymer obtained by the reaction has the best adsorption performance;

[0022] Hollow molecular imprinting polymers can efficiently adsorb and enrich food hazardous substances. The hollow microporous organic material core enhances the hydrophobicity of the material surface and interior, making it more stable in a humid environment and better able to function in organic solvents. It is suitable for the adsorption and enrichment of a variety of food contaminants, opening up a new way for the detection of food hazardous substances. It has important leading significance for further strict monitoring and control of hazardous substances in food and promoting the application of analytical chemistry methodology based on advanced functional materials in food safety and human health science. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Transmission electron microscopy images and dynamic light scattering analysis of hollow microporous network adsorbent materials and molecularly imprinted polymers;

[0024] Figure 2 To evaluate the specificity of hollow molecularly imprinted polymer adsorption materials;

[0025] Figure 3 Evaluation of the repeatability of hollow molecularly imprinted polymer adsorption materials. DETAILED DESCRIPTION

[0026] The embodiments of the present invention are described below with reference to the accompanying drawings.

[0027] The present invention relates to the preparation and application of a hollow molecular imprinted polymer. First, a magnetic composite microporous network adsorption material with strong adsorption and large specific surface area is prepared, and then a hollow microporous network adsorption material is synthesized by HF corrosion, and finally a hollow molecular imprinted polymer adsorption material is obtained by surface molecular imprinting. The prepared hollow molecular imprinted polymer can achieve selective adsorption and efficient enrichment of food and environmental pollutants. Due to its advantages such as larger specific surface area and stronger hydrophobicity, it has great potential as a harmful substance adsorption material. Ensure its stable application in complex food matrices, thereby achieving selective enrichment and convenient control of target pollutants.

[0028] As researchers gradually understand the growth mechanism and microstructure of nanocrystals, hollow nanomaterials have become one of the hot spots in modern nanoscience research. In order to improve the adsorption capacity and the utilization of internal pores, new hollow molecular imprinted polymer materials have been developed to enhance the hydrophobicity of the surface and interior of the material, making it more stable in a humid environment, and better able to play a role in organic solvents, overcome the influence of food matrix on the test results, improve the selectivity of the material for target pollutants, and expand the application of hollow materials. It has a positive impact on improving environmental hygiene and food safety monitoring, and has important guiding significance and social value in promoting the development of efficient detection and evaluation methods for hazards and the effective supervision of food contaminants.

[0029] The present invention aims to etch the magnetic microporous organic network composite material for the first time to obtain a hollow structure microporous network adsorption material, and obtain a hollow molecular imprinted polymer by molecular imprinting, and introduce it into the field of food science research, greatly improving the hydrophobicity and selectivity of the material, and making the adsorption efficiency and repeatability more superior, so as to achieve convenient pretreatment and selective enrichment of target pollutants. A new type of microporous network adsorption material with a hollow structure was constructed by a simple hard template method, and a new type of hollow molecular imprinted polymer was finally obtained by molecular imprinting. The material has a typical hollow structure, a magnetic Fe 3 O 4 The core of the microsphere is wrapped by the metal organic framework material crystal, and then the microporous organic network is introduced into the surface of the metal organic framework material through the sonogashira coupling reaction, and finally the magnetic metal organic framework is etched by hydrofluoric acid. The hollow molecular imprinting polymer adsorption material is obtained by surface molecular imprinting to achieve selective adsorption and efficient enrichment of food and environmental pollutants. Combined with high-performance liquid or gas phase analysis methods, the target pollutants in complex matrix samples are enriched and determined.

[0030] The specific preparation method is as follows:

[0031] Step 1: Using an in-situ growth method to prepare a magnetic composite microporous organic framework material with strong adsorption and large specific surface area;

[0032] Magnetic Fe 3 O 4 Preparation: FeCl 3 6H 2 O, anhydrous sodium acetate and ethylene glycol were mixed and stirred for 60 minutes, then transferred to a Teflon-lined hydrothermal reactor and heated at 200°C for 8 hours. After the reaction was completed and cooled to room temperature, it was washed with ultrapure water 4 times. Then it was vacuum dried at 60°C for 12 hours to collect the black magnetic powder product.

[0033] Magnetic Fe 3 O 4 @SiO 2 Preparation: Take 1.0g of the magnetic Fe obtained in step (1) 3 O 4 , add 200mL HCl, ultrasonically treat for 10min, and then rinse with ultrapure water three times. Add 80mL ultrapure water, 320mL ethanol, 5mL ammonia water, and ultrasonically treat for 10min. Then add 1mL TEOS and stir mechanically for 12 hours. The obtained product is collected with a magnet and rinsed with ultrapure water and ethanol alternately four times.

[0034] Magnetic Fe 3 O 4 @SiO 2@UiO-66-NH 2 Preparation: Take 150 mg of the magnetic Fe obtained in step (2) 3 O 4 @SiO 2 , add 300 mg zirconium (IV) chloride, 75 μL water, and 30 mL DMF and stir for 15 min. Then, add 2-aminoterephthalic acid and stir until completely dissolved. Transfer the above solution to a Teflon-lined hydrothermal reactor and heat at 120°C for 24 hours. After cooling to room temperature, collect the brown-black magnetic microspheres and rinse them with ultrapure water several times. Finally, dry the product under vacuum at 60°C for 12 hours.

[0035] Magnetic Fe 3 O 4 @SiO 2 @UiO-66-NH 2 Preparation of @MON: Take 200 mg of Fe obtained in step (3) 3 O 4 @SiO 2 @UiO-66-NH 2 , add 15mL toluene, 15mL triethylamine and an appropriate amount of catalyst, and ultrasonicate for 30 minutes, wherein the catalyst and dosage are 3.4mg bis(triphenylphosphine)palladium(II) dichloride and 1.0mg cuprous iodide. After complete dispersion, mechanically stir at 90℃ for 30min, add 50mg tetra(4-ethynylphenyl)methane and 80mg1,4-diiodobenzene, and continue to heat at 90℃ for 6 hours. After the reaction system is cooled to room temperature, collect the product with a magnet, wash it with dichloromethane and methanol five times, and dry it in vacuum at 50℃. The obtained brown-black powder is the magnetic composite microporous network adsorption material Fe 3 O 4 @SiO 2 @UiO-66-NH 2 @MON.

[0036] Step 2: Synthesize hollow microporous network adsorption material by HF corrosion; Take 100.0 mg of Fe 3 O 4 @SiO 2 @UiO-66-NH 2 @MON, add 10 ml HF (5%) and react for 15 min. After washing with ethanol and water five times, dry in vacuum at 50°C. The obtained black powder is the hollow structure microporous network adsorption material HMON.

[0037] Step 3: Obtain hollow molecular imprinting polymer adsorption material by surface molecular imprinting; 1mmol DT is added to a mixture of 25mL acetonitrile and 5mL water, and stirred with a magnetic stirrer until completely dissolved. Next, different proportions of functional monomer (APTES), crosslinker (TEOS) and ammonia water are mixed into the system, preferably, the molar ratio of functional monomer (APTES), crosslinker (TEOS) and ammonia water is 1:4:9. After uniform mixing, 3mL HMON dispersed in acetonitrile is added. Subsequently, nitrogen is continuously passed through the entire reaction system for 15 minutes to remove oxygen. Finally, the flask is sealed and stirred at room temperature overnight. The obtained precipitate is washed three times with methanol and water. Then it is eluted with a Soxhlet extraction apparatus. The eluent consists of acetone and acetic acid (9:1, v / v). The obtained solid is the hollow molecular imprinting polymer HMON@MIP.

[0038] The prepared hollow molecular imprinted adsorption material has good particle size uniformity, has significant specific adsorption capacity for target pollutants, and the hollow structure of the material greatly increases the density of imprinted sites, thereby improving the adsorption efficiency. At the same time, the hollow microporous organic material core enhances the hydrophobicity of the surface and interior of the material, making it more stable in a humid environment and better able to play a role in organic solvents, and is suitable for the adsorption and enrichment of a variety of food pollutants.

[0039] The porous network adsorption materials that have been reported, such as metal organic framework materials and hyper-crosslinked polymer materials, have the defects of poor stability, cumbersome synthesis process, poor adsorption capacity, etc., and their application in practice is very limited. The hollow microporous network adsorption material prepared by the present invention has the advantages of high porosity, large specific surface area, and good chemical stability. It can give full play to the efficient adsorption performance of porous materials and ensure its stable application in complex food matrices, thereby achieving efficient enrichment and convenient control of target pollutants.

[0040] Combined with high performance liquid or gas phase analysis methods, the target pollutants in complex matrix samples can be enriched and determined.

[0041] The scheme of the present invention is described below in conjunction with the accompanying drawings, wherein the experimental methods without specific operating steps are all carried out in accordance with the corresponding product instructions, and the instruments, reagents, and consumables used in the examples can all be purchased from commercial companies unless otherwise specified.

[0042] Example 1: Preparation of hollow molecularly imprinted polymers

[0043] Firstly, an in-situ growth method is used to prepare a magnetic composite microporous network material with strong adsorption and large specific surface area.

[0044] Magnetic Fe 3 O 4Preparation: 27g FeCl 3 6H 2 O, 57.5 g of anhydrous sodium acetate, and 500 mL of ethylene glycol were mixed and stirred for 60 minutes, then transferred to a Teflon-lined hydrothermal reactor and heated at 200°C for 8 hours. After the reaction was completed and cooled to room temperature, it was washed with ultrapure water 4 times. Then it was vacuum dried at 60°C for 12 hours to collect a black magnetic powder product.

[0045] Magnetic Fe 3 O 4 @SiO 2 Preparation: Take 1.0g of the magnetic Fe 3 O 4 , add 200mL HCl (0.1mol / L), ultrasonically treat for 10min, and then rinse with ultrapure water three times. Add 80mL ultrapure water, 320mL ethanol, and 5mL ammonia water (concentration 25-28%), and ultrasonically treat for 10min. Then add 1mL LTEOS and stir mechanically for 12 hours. The obtained product was collected with a magnet and rinsed with ultrapure water and ethanol alternately four times.

[0046] Magnetic Fe 3 O 4 @SiO 2 @UiO-66-NH 2 Preparation: Take 150 mg of the magnetic Fe 3 O 4 @SiO 2 , add 300 mg of zirconium (IV) chloride, 75 μL of water, and 30 mL of DMF and stir for 15 minutes. Then, add 235 mg of 2-aminoterephthalic acid and stir until completely dissolved. Transfer the above solution to a Teflon-lined hydrothermal reactor and heat at 120°C for 24 hours. After cooling to room temperature, collect the brown-black magnetic microspheres and rinse them several times with ultrapure water. Finally, dry the product under vacuum at 60°C for 12 hours.

[0047] Magnetic Fe 3 O 4 @SiO 2 @UiO-66-NH 2 @MON preparation: Take 200 mg Fe 3 O 4 @SiO 2 @UiO-66-NH 2, add 15mL toluene, 15mL triethylamine and 3.4mg bis(triphenylphosphine)palladium(II) dichloride, 1.0mg cuprous iodide, and ultrasonicate for 30min. After complete dispersion, mechanically stir at 90℃ for 30min, add 50mg tetra(4-ethynylphenyl)methane and 80mg 1,4-diiodobenzene, and continue heating at 90℃ for 6 hours. After the reaction system is cooled to room temperature, collect the product with a magnet, wash it with dichloromethane and methanol five times, and dry it in vacuum at 50℃. The brown-black powder obtained is the magnetic composite microporous network adsorption material Fe 3 O 4 @SiO 2 @UiO-66-NH 2 @MON.

[0048] The hollow microporous network adsorption material was synthesized by HF etching. 100.0 mg Fe 3 O 4 @SiO 2 @UiO-66-NH 2 @MON, add 10 ml HF (5%) and react for 15 min. After washing with ethanol and water five times, dry in vacuum at 50°C. The obtained black powder is the hollow structure microporous network adsorption material.

[0049] Hollow molecular imprinting polymer adsorption materials were obtained by surface molecular imprinting. 1mmol 1,4-dihydroxyanthraquinone DT was added to a mixture of 25mL acetonitrile and 5mL water and stirred with a magnetic stirrer until completely dissolved. Next, functional monomer (APTES), crosslinker (TEOS) and ammonia water were added to the system in a molar ratio of 1:4:9. After uniform mixing, 3mL HMON dispersed in acetonitrile was added. Subsequently, nitrogen was continuously passed through the entire reaction system for 15 minutes to remove oxygen. Finally, the flask was sealed and stirred at room temperature overnight. The obtained precipitate was washed three times with methanol and water. Then it was eluted with a Soxhlet extraction apparatus. The eluent consisted of acetone and acetic acid (9:1, v / v). The obtained solid was the hollow molecular imprinting polymer HMON@MIP.

[0050] The prepared product was characterized and the results were as follows Figure 1 As shown, Figure 1 A is the transmission electron microscope and scanning electron microscope images of a series of intermediate materials in the preparation process of HMON@MIP. Figure 1 B is the dynamic light scattering analysis of the hollow microporous network adsorbent material and the molecular imprinting polymer, indicating that the prepared hollow adsorbent material has better particle size uniformity, with a size of about 600 nm.

[0051] Example 2: Adsorption and enrichment of pollutants by hollow molecularly imprinted polymers

[0052] The material obtained in Example 1 is placed in a solution of sterigmatotoxin ST to achieve enrichment of sterigmatotoxin ST. Quantitative detection can be performed in combination with high performance liquid chromatography.

[0053] In order to verify the specificity of the hollow molecular imprinted polymer, the same steps were followed to place equal amounts of the hollow molecular imprinted polymer in standard solutions of ochratoxin A, aflatoxin B1, aflatoxin B2, aflatoxin M1, microcystin LR, vomitoxin DON and zearalenone ZEN to achieve adsorption of these interfering toxins. Figure 2 As shown, the specificity evaluation of the hollow molecular imprinted polymer adsorption material indicates that the prepared hollow adsorption material has good adsorption performance only for ST, proving the strong specificity of the material.

[0054] Example 3: Investigation of the repeatability of hollow molecularly imprinted polymers

[0055] The hollow adsorbent material obtained in Example 1 was eluted and ultrasonicated for 20 minutes until no adsorbed target was detected in the supernatant. The thoroughly cleaned material was placed in a vacuum oven and dried overnight at 40°C. The dried material was subjected to the same adsorption-elution-analysis steps as before, and the average value of three parallel determinations was obtained. This was repeated 20 times, and the recovery rate of the target was compared each time. The results are shown in Figure 3 As shown, the results show that the prepared hollow adsorption material has good reusability, and a high recovery rate can still be obtained after 20 consecutive uses, and can be applied to actual samples.

[0056] The embodiments of the present invention are described in detail above, but the contents described are only preferred embodiments of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.

Claims

1. A method for preparing a hollow molecularly imprinted polymer, characterized in that: The magnetic composite microporous network adsorption material is prepared, the hollow microporous network adsorption material is synthesized by HF corrosion, and the hollow molecular imprinted polymer adsorption material is obtained by surface molecular imprinting.

2. The method for preparing a hollow molecularly imprinted polymer according to claim 1, characterized in that: The specific steps include: Step 1: Prepare magnetic composite microporous organic framework material by in-situ growth method; Preparation of magnetic Fe3O4: FeCl3·6H2O, anhydrous sodium acetate and ethylene glycol are mixed and subjected to hydrothermal reaction at 200℃, and the product is washed and dried to obtain magnetic Fe3O4; Preparation of magnetic Fe3O4@SiO2: Take 1.0g of magnetic Fe3O4, add 200mL HCl, ultrasonically treat, rinse the product, add 80mL ultrapure water, 320mL ethanol, 5mL ammonia water, and ultrasonically treat; then add 1mL TEOS, stir mechanically, collect the obtained product with a magnet, and obtain magnetic Fe3O4@SiO2; Preparation of magnetic Fe3O4@SiO2@UiO-66-NH2: Take 150 mg of magnetic Fe3O4@SiO2, add 300 mg of zirconium (IV) chloride, 75 μL of water, and 30 mL of DMF, stir, add 2-aminoterephthalic acid, stir and dissolve; perform hydrothermal reaction at 120 °C, collect brown-black magnetic microspheres after the reaction is completed, rinse and dry to obtain magnetic Fe3O4@SiO2@UiO-66-NH2; Preparation of magnetic Fe3O4@SiO2@UiO-66-NH2@MON: Take 200 mg of Fe3O4@SiO2@UiO-66-NH2, add 15 mL of toluene, 15 mL of triethylamine and a catalyst, and stir mechanically at 90 ° C for 0.5 h after complete dispersion. Add 50 mg of tetrakis(4-ethynylphenyl)methane and 80 mg of 1,4-diiodobenzene, and heat at 90 ° C for 6 h. After the reaction is completed, collect the product with a magnet, wash and dry to obtain the magnetic composite microporous network adsorption material Fe3O4@SiO2@UiO-66-NH2@MON; Step 2: Synthesize hollow microporous network adsorption material by HF corrosion; take 100.0 mg Fe3O4@SiO2@UiO-66-NH2@MON, add 10 ml HF (5%) to react for 15 min, wash and dry to obtain hollow structure microporous network adsorption material HMON; Step 3: Obtain hollow molecular imprinting polymer adsorption material by surface molecular imprinting; add 1mmol DT to a mixture of 25mL acetonitrile and 5mL water and mix well, add functional monomer (APTES), crosslinker (TEOS) and ammonia water into the system at a ratio of 1:4:9; after mixing evenly, add 3mL HMON dispersed in acetonitrile; remove oxygen from the reaction system and stir at room temperature overnight, and the obtained precipitate is the hollow molecular imprinting polymer HMON@MIP.

3. The method for preparing a hollow molecularly imprinted polymer according to claim 2, characterized in that: The catalyst used in the preparation of magnetic Fe3O4@SiO2@UiO-66-NH2@MON in step 1 is 3.4 mg of bis(triphenylphosphine)palladium(II) dichloride and 1.0 mg of cuprous iodide.

4. The method for preparing a hollow molecularly imprinted polymer according to claim 2, characterized in that: The drying temperature is 50-60℃.

5. The method for preparing a hollow molecularly imprinted polymer according to claim 2, characterized in that: In step 3, the product obtained by stirring overnight is washed with methanol and water, and then eluted with a Soxhlet extraction apparatus, and the eluent is composed of acetone and acetic acid (9:1, v / v).

6. A hollow molecularly imprinted polymer prepared by the method for preparing a hollow molecularly imprinted polymer according to any one of claims 1 to 5.

7. Use of the hollow molecularly imprinted polymer according to claim 6 in the adsorption or detection of food or environmental pollutants.

8. The use according to claim 7, characterized in that: The obtained hollow molecular imprinting polymer material is placed in a target solution to achieve adsorption or enrichment of pollutants.

9. The use according to claim 6, characterized in that: The adsorbed hollow molecular imprinted polymer can be used again for adsorption or enrichment of pollutants after being eluted by an eluent.

Citation Information

Patent Citations

  • Ochratoxins upconversion fluorescent sensing material and preparation method thereof

    CN105300948A

  • Preparation method and application of long-afterglow molecularly imprinted polymer

    CN110665480A

  • Preparation method and application of hollow-structure microporous network adsorption material

    CN115254031A

  • Nicotinamide virtual template surface molecularly imprinted material and preparation method therefor and application thereof

    WO2021103622A1